Peace Building and Social Media in a Cosmopolitan Society - I. Omotayo Adeshina (International Studies Journal)
The aim or purpose of peacebuilding is to address the root causes of conflict create and promote peace. Peace is built on social, political, economic and ecological foundations that serve the welfare of the people. Many demonstrations, protests and social movements which utilises the use of non-violence has led some approaches to peacebuilding to focus not only on the root cause(s) of conflict but also on good governance and peaceful dispute settlement mechanisms. Social media platforms such as Twitter, Facebook and WhatsApp, among others, provide a space in which society can communicate freely and cheaply, articulating their divergent viewpoints. Social media has now become a new marketplace of ideas, equally disliked and needed by politicians, diplomats, international institutions, civil society groups and violent groups alike. Africa represents a cosmopolitan society given its multi-cultural and multi-ethnic richness. Nigeria is the most heterogeneous and multicultural society in Africa with over 300 ethnic nationalities and concurrent religious diversities. In Nigeria, individualism, ethnicity and tribalism are more prevalent than cosmopolitan ideas of universality and generality. Cosmopolitanism embraces an individual's willingness to engage with people of different tribes and culture while upholding universal standards of human rights. Social media has birthed the idea of virtual cosmopolitanism and the construction of virtual cultures. This article seeks to explore various means by which peacebuilding can be achieved through social media in a global and cosmopolitan era.